CHANGES IN PHOTOSYNTHETIC ACTIVITY AND NUTRITIONAL PROCESSES UNDER THE INFLUENCE OF BIOPREPARATIONS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The study presents the effects of biopreparates based on zirconium protective-stimulatory complexes and mixtures on photosynthetic activity, seed quality, growth, development, and productivity of spring barley. A high correlation between leaf surface area and yield was established.
Keywords: Biopreparates, photosynthetic activity, plant growth regulators, spring barley, leaf surface, productivity.